Определение информативных показателей при дифференциальной диагностике дерматологических заболеваний - Печерская, А. И. (ХНУРЭ, 2008)
The given work is devoted to the definition of informative indexes for differential diagnostics in the field of dermatology. It is suggested to use an informative criterion, possessing entropy properties, for the decision the task of exposursng informing sparks for differentiation of skin diseases. Expedience of application of this criterion is conditioned by its efficiency and insensitivity to measuring units of spark.
Keywords: диагностике заболеваний; дерматология